Pendudukan Wilayah Oleh Negara Musuh dan Pelaksanaan Referendum - Salampessy, Sal Sabila; Tuhulele, Popi; Daties, Dyah Ridhul Airin (PATTIMURA Law Study Review, 2025)
Occupation is a form of sovereignty enforcement over a territory that is not under the control of another state, and the UN Charter prohibits the acquisition of territory by force. The referendum conducted by Russia in Ukrainian territory constitutes a violation of Article 2(4) of the UN Charter, UN General Assembly Resolution Number 2625 of 1970, and UN General Assembly Resolution Number 2131 of 1965 on the prohibition of intervention in the internal affairs of other states. The principle of self-determination through a referendum should be conducted without external interference and in accordance with international law. This research employs normative legal methods with case and legislative approaches to examine the regulations regarding referendums in international law and the feasibility of conducting them in enemy-occupied territories. The findings indicate that a referendum cannot be lawfully conducted in an enemy-occupied territory as it violates fundamental principles of state sovereignty, territorial integrity, and the non-intervention principle in international law. Concrete examples, such as the referendums conducted by Russia in Crimea and the regions of Donetsk, Lugansk, Kherson, and Zhaporizhia, illustrate violations of international law, with the results of these referendums being legally unrecognized by the international community.